Multitemporal analysis of changes in vegetation cover in the municipality of Novo Repartimento, Pará (Research, Society and Development, 2022)
This work aimed to analyze the changes in the vegetation cover of the municipality of Novo Repartimento, Southeast of Pará, for the years 2017, 2018 and 2019, using the ENVI 5.3 software to perform the processing using the supervised classification methods and the respective procedures performed to perform the analysis in the area of ​​interest, as well as using ArcGIS 10.5 software to quantify and produce the final maps. The study area was the municipality of Novo Repartimento, with the delimited area, we sought to download the scenes for the respective years of 2017, 2018 and 2019. Three scenes were downloaded from the Landsat 8 satellite, with the orbits points: 224063 , 224064 and 225063, for the respective years. When analyzing all the classifications, it can be concluded that for the area under study the most suitable classification is Mahanalobis, because it managed to distinguish well the forest from the secondary vegetation area, as well as the anthropic cloud area, presenting very well the roads that pass between the municipality.